Heterogeneity of tumour infiltrating lymphocytes (TILs) in breast cancer and its prognostic significance - Althobiti, Maryam; Aleskandarany, Mohammed A.; Joseph, Chitra; Toss, Michael S.; Mongan, Nigel P.; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ashankyty, I.; Ellis, Ian O.; Green, Andrew R.; Rakha, Emad A. (Wiley, 2018)
Background: Tumour-infiltrating lymphocytes (TILs) in breast cancer (BC) confer prognostic and predictive information. This study aims to assess the spatial and temporal heterogeneity of TILs in BC and its relationship with immune cell subtypes.